2011
DOI: 10.1016/j.cell.2011.11.041
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between Differentiating Cell- and Niche-Derived Signals in Hematopoietic Progenitor Maintenance

Abstract: Summary Maintenance of a hematopoietic progenitor population requires extensive interaction with cells within a microenvironment or niche. In the Drosophila hematopoietic organ, niche-derived Hedgehog signaling maintains the progenitor population. Here we show that the hematopoietic progenitors also require a signal mediated by Adenosine deaminase growth factor A (Adgf-A) arising from differentiating cells that regulates extracellular levels of adenosine. The adenosine signal opposes the effects of Hedgehog si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

12
238
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 182 publications
(251 citation statements)
references
References 51 publications
12
238
0
1
Order By: Relevance
“…However, Pvr overexpression did restore the ARF1-depleted niche loss, indicating that an alternate mechanism for STAT activation may operate from the CZ or circulating hemocytes. The control of AdgfA activity by Stat has been demonstrated (25). We have shown that Stat92e activation is mediated by Asrij (7).…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…However, Pvr overexpression did restore the ARF1-depleted niche loss, indicating that an alternate mechanism for STAT activation may operate from the CZ or circulating hemocytes. The control of AdgfA activity by Stat has been demonstrated (25). We have shown that Stat92e activation is mediated by Asrij (7).…”
Section: Discussionmentioning
confidence: 74%
“…Prohemocyte maintenance is achieved by a balanced response to signals from the niche and from differentiated cells of the CZ (25). Because ARF1 depletion in the CZ affects niche maintenance non-cell autonomously and also results in induction of differentiation, we studied the effect of modulating ARF1 levels on the Pvf/Pvr/Stat/ AdgfA axis that signals from the niche to the CZ and back to MZ prohemocytes (25). Because Asrij has a conserved role in endosomally regulating JAK/STAT signaling to maintain stem cell potency in Drosophila hematopoiesis, we investigated whether ARF1 is involved in this axis.…”
Section: Perturbation Of Arf1 and Its Activated Form Leads To Aberranmentioning
confidence: 99%
“…In addition, Trol regulates PDGF signaling in plasmatocytes (12). PDGF-like factors and their receptors, PDGF/VEGF receptors, are involved in hemocyte production in the Drosophila embryo (13)(14)(15). The interaction between Trol and the PDGF/VEGF receptor signaling pathway participates in hemocyte homeostasis in Drosophila (11,12).…”
mentioning
confidence: 99%
“…3 Also, differentiated blood cells feedback on prohemocytes to keep them undifferentiated. 6 In addition, a compact extracellular matrix (ECM) is observed around the Medullary Zone/prohemocytes and modulating ECM composition affects prohemocyte maintenance. 7 Furthermore, one could speculate that cells of the cardiac tube that are lining the LG participate in prohemocyte maintenance.…”
mentioning
confidence: 99%